Pengaruh Pijat Bayi Kombinasi Aromatherapy Peppermint terhadap Gejala Batuk Pilek pada Balita Usia 1-5 Tahun - Yenni Puspita; Eva Susanti (Poltekkes Kemenkes Padang, 2026)
Background: Cough and cold are common complaints among toddlers and are symptoms of Upper Respiratory Tract Infections (URTI), which can disrupt children’s comfort and daily activities. The cough and cold massage therapy is a non-pharmacological method believed to help relieve symptoms by improving blood circulation and boosting the immune system. Objective: This study aimed to determine the effectiveness of cough and cold massage therapy in reducing the duration of symptoms in toddlers. Methods: The study used a pre-experimental design with a one-group pretest–posttest approach. A total of 64 toddlers aged 1–5 years experiencing cough and cold were selected using a purposive sampling technique. Data were collected using questionnaires to record respondents’ characteristics and symptom observations before and after the intervention. The research was conducted from July to September 2025. Data were analyzed using the Wilcoxon test. Results: The findings showed a significant difference before and after the cough and cold massage therapy, with aromatherapy peppermint a p-value of 0.000 (<0.05), indicating that the therapy effectively accelerated recovery. Cough and cold massage therapy can serve as a non-pharmacological alternative to help reduce cough and cold symptoms in toddlers. Conclusion: This method is recommended for use by parents and healthcare providers as a promotive and preventive effort to improve children’s health.